2022
DOI: 10.5935/1984-0063.20220035
|View full text |Cite
|
Sign up to set email alerts
|

‘I love you’: the first phrase detected from dreams

Abstract: Objective Many people have dreams nightly and some maintain consciousness during dreams. Such dreams are referred to as lucid dreams (LD). During dreams, our speech correlates with facial muscle activity, which is hard to decode, but LD could solve this problem. The primary hypothesis of this study was that the facial muscles electric activity during LD corresponds to specific sounds. Understanding this connection could help decode dream speech in the future. Material and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…While in LDs, people can use their breath or muscles to send signals through EMG sensors and transfer whole words in Morse code (LaBerge et al, 1981). EMG sensors can also help decode speech in LDs because it has the same patterns as vocalizations in wakefulness (Raduga, 2022). EEG can also be intentionally affected in LDs (Erlacher et al, 2003), as can the facial muscles responsible for emotions (Konkoly et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While in LDs, people can use their breath or muscles to send signals through EMG sensors and transfer whole words in Morse code (LaBerge et al, 1981). EMG sensors can also help decode speech in LDs because it has the same patterns as vocalizations in wakefulness (Raduga, 2022). EEG can also be intentionally affected in LDs (Erlacher et al, 2003), as can the facial muscles responsible for emotions (Konkoly et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… 37 This PACMs method is effective when studies require many cords and sensors besides PSG. 38 However, the main problem with this method is that it may be hard to differentiate genuine muscle atonia from deep relaxation or the N3 stage of non-REM sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings are important regarding the topic of the present study, as since the 1970s, facial EMG activity has also been associated with speech in dreams (McGuigan & Tanner, 1971; Oldis, 2017; Shimizu & Inoue, 1986). Moreover, in 2021, it was shown that the phrase I love you vocalized in LDs had the same facial EMG pattern as real-life vocalization (Raduga, 2022a).…”
mentioning
confidence: 99%
“…Second, all EMG speech recognition studies have focused on a few specific languages, which could increase the error rate among nonnative speakers. According to the abovementioned study on speech recognition for the phrase I love you in LDs, a constructed language based only on EMG distinctive sounds could help to unmute people in LDs, as the words could be automatically decoded in reality (Raduga, 2022a).…”
mentioning
confidence: 99%